A STUDY OF GEOMETRIC DESIGN OF ROADWAY USING CIVIL 3D 2020 - Akash Surendra Kolamkar; Prof. Kalyani P. Nichat (International Engineering Journal For Research & Development, 2021)
India is a country whose population is growing rapidly, indicating that traffic is also increases. The development of rural areas also increases its means furthering of transportation facilities are also developed. The geometric design manages the dimensions and layout of visible features of the road such as alignment, sight distance, cross-section, and intersections. The basic object is optimizing efficient traffic and safety of highway and minimizing cost and environmental damages. Design the road knows about the fundamental of road geometric and next step to upgrade their value is by learning software for use of the essential information. Geometric Design of road involves such tasks as creating the road alignment and plotting the alignment profile using bearings or coordinates (easting and northing), stations and elevations of points along the proposed route, lengths of vertical curves, computation of earthwork quantities, and numerous other analyses and calculations aimed at finding the optimum alignment while satisfying design standards and constraints. When geometric design performed manually, it is time-consuming and highly susceptible to very costly errors. In the present time, various software is available in market such as Bentley MX Road, AutoCAD Civil 3D, etc. are used to design the geometry of road. Current patterns are adapted to the utilization of computer programs for roadway geometry design. This dissertation presents a complete geometric design of road project using AutoCAD Civil 3D software. The main aim of the project is to display how geometric design can be performed in a very short time with accuracy. The road design procedure using AutoCAD Civil 3D has been presented. This software provides clarity, save times and effort to a user. Civil 3D is software for engineering it is used for the design, plan and manage the civil engineering works. This software is generally used by experts and civil engineers.